The role of football school in maximizing students' talent to play football in kampak district - Bismi Aulia Nurrohman; Muhammad Soleh Fudin; Sugeng Sulendro (PHEDHERAL, 2022)
The focus of the research is how is the role of SSB Permata Kampak in maximizing the talents of students playing football in Kampak sub-district. The purpose of this study was to determine the role of SSB Permata Kampak in maximizing the talents of students playing football in Kampak sub-district. This research uses a type of qualitative research that is descriptive. The determination of informants was carried out purposively with the unit of data analysis being an institution, namely SSB Permata Kampak. Data collection was obtained through in-depth interviews and direct observation. Data were analyzed qualitatively through three stages, namely reduction, presentation, and conclusion. The conclusion in this study is the role of SSB Permata Kampak in maximizing the talent of students playing football which includes 1) the SSB Permata Kampak development program must have a talent development curriculum that is documented as a guideline for the implementation of coaching; 2) coaching requires collaboration with related parties, especially parents and guardians of students; 3) trainers at SSB Permata Kampak carry out self-development regarding science and technology in coaching science; 4) the SSB Permata Kampak training program has been going well, but the trainers are more creative and adaptive in making training programs to minimize obstacles during practice; 5) the facilities and infrastructure are sufficient but SSB Permata Kampak is trying to carry out maintenance and rejuvenation so that the training can take place effectively and efficiently.